Promoting Reading Comprehension by Using Socratic Questioning - Lida Holida Mahmud; Tryana Tryana (Universitas Cokroaminoto Palopo, 2023)
The purpose of this study is to describe the atmosphere in improving reading comprehension of Pamulang University students in reading class using Socratic questioning method. The study emphasized the technique of reading comprehension by promoting Socratic Question. It particularly focused on helping students’ achievement in Reading Comprehension. The subjects of this study were second semester students from the English Department at Pamulang University. Two cycles of Classroom Action research were conducted by implementing the actions, observing the class and analyzing the results. The instruments used in this study were observation lists, questionnaires and reading tests. The data were analyzed qualitatively. Based on the data analysis it was found that Socratic Questioning promoted reading comprehension. It is presented on improvement in mean score between pre and posttest in the first phase. In the second phase, the differing mean score was likewise seen. This improvement shows that students learn that by implementing Socratic questioning on the text given. It also leads to the conclusion that the Socratic questioning method encourages them to ask questions, meaning that the Socratic questioning method stimulates their critical thinking to think about the text they read and guides them to comprehend the text.